Reflective Practice and Factors Affecting it: Perceptions of Pediatric Surgery Residents - Naumeri, Fatima (Annals of King Edward Medical University, 2023)
Background: There is scarcity of literature about factors affecting reflective practices in local context. By focusing on these factors, we can help promote engagement in reflective practices in our culture. Objective of this study was to explore the barriers to and facilitators of reflective practice by post graduate surgical residents. Methods: Using action research study design, qualitative research was conducted in the department of Pediatric Surgery, Mayo Hospital to explore different factors affecting reflective practice in postgraduate surgical residents in their daily practice. A workshop on reflective practices was conducted, followed by weekly morbidity/mortality meetings and case-based discussions deliberating using Gibbs' reflective cycle. After a year, focus group discussion using a heterogenous group of nine residents was conducted to explore the factors affecting reflective practice. It was transcribed and analyzed thematically. Results: Reflective practice was perceived to improve critical appraisal, deeper learning, self-monitoring, and patients' outcomes. There was resistance towards reflective writing. Themes related to factors affecting reflective practice were organization, time allocation, communication, workplace environment, interpersonal relations, guided reflection, and feedback. Involvement of multiple disciplines in 'reflection before action' was identified for future implementation. Conclusion: Provision of guided reflection and constructive feedback were the main facilitators of reflective practice. Generally, improving organization, workplace environment, interpersonal relations, and accommodating individual learning styles can enhance reflective practice in our context, and help developing habit of lifelong learning.